Indigofera: “Kini dan Nanti” - MUZAYYINAH MUZAYYINAH (Bioedukasi: Jurnal Pendidikan Biologi, 2014)
Indigofera tinctoria as one of natural blue  dyes that has been since the 4th century inIndonesia. The use of natural dyes in decline with synthetic dyes. An effort to prevents carcity of I.tinctoria as natural dyes among others cultivation, use of marginal lands as Indigofera cultivation location, and genetic engineering to get a superior species.